Community-Based Empowerment: Semi-Systematic Literature Review (SSLR) - Dwi Prasetyani; Rian Destiningsih; Amelia Choya Tia Rosalia (Universitas Ahmad Dahlan, 2022)
The purpose of this study was to synthesize research results with the topic of community-based community empowerment in Indonesia using the Scopus database. The method used is a semi-systematic literature review (SSLR). Semi-systematic analysis shows that there are two main themes, namely the identification of scientific journals that contain articles on the topic of community-based community empowerment in Indonesia and the phenomenon of community-based community empowerment in Indonesia from previous studies. The findings in this study are publications on the topic of community-based community empowerment in Indonesia, the phenomenon of community-based community empowerment in Indonesia still can be explored more deeply considering the surge in articles related to this topic in 2020; Community empowerment is one of the strategies to reduce poverty in Indonesia. As a coping strategy, community empowerment is also provided with related regulations. The National Program for Independent Community Empowerment, empowerment of microfinance institutions (LKM), and micro-credit schemes and tourist villages are examples of the application of the concept of community empowerment in Indonesia, but the application still requires some improvements, for example by considering social capital such as local institutions, local wisdom Local customs, norms, and customs as an effort to apply the concept of community empowerment are getting closer to the main goal, namely reducing poverty and improving community welfare.